To Boldly Go Where No Data Stream Has Gone Before - Pearson, Ezzy (Patterns (N Y), 2020)
As humanity explores the Solar System, the further our spacecraft get from Earth the further their data signals have to travel. We look at some of the biggest obstacles that come up when attempting to transfer data billions of kilometers across space using a power- and weight-limited spacecraft.